Complete mitochondrial genome of Lasiopodomys mandarinus mandarinus (Arvicolinae, Rodentia). (3rd March 2016) - Li, Yangwei; Lu, Jiqi; Wang, Zhenlong
Abstract: Mandarin voles ( Lasiopodomys mandarinus ) is a subterranean rodent species that are often used as a model for studying subterranean hypoxic stress in mammals. Its subspecies L. m. mandarinus span in cropland in most area of north China and is regarded as an agricultural pest. In this paper, the complete mitochondrial genome of L. m. mandarinus has been determined. Our results showed that the mitochondrial genome of L. m. mandarinus is a circular molecule of 16 367 bp, which contents 13 protein-coding, 22 tRNAs and 2 rRNAs genes. The overall base composition of the heavy strand is 32.47% A, 27.04% T, 27.01% C, and 13.47% G. with an AT content of 59.51%.